Matrix metalloproteinase-9 Gene-1562C>T Gene Polymorphism and Coronary Artery Disease in the Chinese Han Population: A Meta-Analysis of 5468 Subjects - Li, Yan-Yan; Yang, Xin-Xing; Zhou, Yan-Hong; Gong, Ge; Geng, Hong-Yu; Kim, Hyun J.; Zhou, Chuan-Wei; Qian, Yun; Wang, Xiang-Ming; Wu, Jun (Frontiers in Physiology, 2016)
Background: Multiple studies indicate that the matrix metalloproteinase-9 (MMP-9)-1562C>T gene polymorphism may be associated with an increased risk of coronary artery disease (CAD) in the Chinese Han population. However, a clear consensus has yet to be established. Objective and methods: A meta-analysis of 5468 subjects from 10 separate studies was performed to explore the possible relationship between the MMP-9-1562C>T gene polymorphism and CAD within the Chinese Han population. Pooled odds ratio (ORs) for the association and the corresponding 95% confidence intervals (CIs) were evaluated by a random or fixed-effect model. Results: Our analysis confirms the association between the MMP-9-1562C>T gene polymorphism and an increased risk of CAD within the Chinese Han population under allelic (OR: 1.60, 95% CI: 1.25–2.04, P = 0.0002), recessive (OR: 3.05, 95% CI: 1.67–5.56, P = 0.0003), dominant (OR: 2.23, 95% CI: 1.49–3.35, P = 0.0001), homozygous (OR: 3.41, 95% CI: 1.87–6.23, P < 0.0001), heterozygous (OR: 2.03, 95% CI: 1.40–2.93, P = 0.0002), and additive genetic models (OR: 1.78, 95% CI: 1.33–2.39, P < 0.0001). Conclusions: In the Chinese Han population, the MMP-9-1562C>T gene polymorphism is correlated with an increased risk of CAD. Therefore, Han Chinese carriers of the -1562T allele may be at an increased risk of CAD.